Pengaruh Program Kampus Mengajar Angkatan IV dalam Meningkatkan Kompetensi Literasi dan Kompetensi Numerasi Siswa SMP Terpadu Al-Bukhari Muslim Medan Tahun Ajaran 2022/2023 - Mian Siahaan; Dapot Tua Manullang; Vina Merina Br Sianipar; Rinawati Lumbansiantar (Departement of Mathematics Education, 2023)
The aims of this study were to determine: (1) The Effect of the Teaching Campus Program on Students' Literacy Competence; (2) The Influence of the Teaching Campus Program on Students' Numeral Competence. This research was conducted at SMP Al Bukhari Muslim Medan T.A 2023/2024. The population in this study were all students of SMP Al Bukhari Muslim Medan, totaling 55 people and some of the teachers totaling 14 people. The sampling technique used the total sample method. Data collection techniques using a questionnaire (questionnaire). Test the validity by using the product moment analysis technique and the reliability of the questionnaire using the Alpha Croanbach formula. The data analysis technique used is simple linear regression analysis. The results of the study show that: (1) the Teaching Campus Program has a positive and significant effect on Literacy Competence with tcount > ttable. (4.142 > 1.674) and a significance value of 0.001 <0.05; (2) the Teaching Campus Program has a positive and significant effect on Numeral Competence with tcount > ttable. (4.555 > 1.674) and a significance value of 0.001 <0.05. The resulting simple linear regression equation for the variable Literacy Competency (Y1) is Y = 46.244 + 0.003 X and for vairabel Numeration competence (Y2) is Y = 43.471 + 0.002 X.